“FOR THE CULTURE, TOWARDS THE HYGIENE”: PUBLIC HEALTH AND “THE EXHIBITIONARY COMPLEX” IN LVIV IN THE LATE XIXTH – EARLY XXTH CENTURY (City: History, Culture, Society, 2019)
The long XIX century became «the golden age» in the history of exhibitions. During that period of time, understanding of their meaning, organizational approaches and thematical content changed, thus they received new functions. Quite often these processes are considered and explained within the framework of the concept of «the exhibitionary complex». The development of public health, its inclusion into the list of the indices of «civilization»and «progress», high prestige of the hygiene and hygienists, and «bacteriological revolution» contributed to the emergence of separate international, national and regional exhibitions that focused on public health and hygiene in the second half of the XIXth century.Two exhibitions, dedicated to medicine and natural science, that was held in Lviv in 1888 and 1907, echoed and followed the international trends. Although they did not focus exclusively on hygiene and public health, separate departments and sections were devoted to these issues. Both Lviv exhibitions were organized by professionals within the scope of the congresses of Polish physicians and naturalists, and thus they had both local and national character.The separation of hygiene as an autonomous part of these exhibitions should be considered in connection with two phenomena. The first was the development of the hygiene movement in Galicia during that time. Hygienists, among other purposes, sought to spread «hygienic education» among broad strata of society. The second was the shaping of public discourse on public health in the province of Galicia. Additionally, exhibitions became a site of cooperation between authorities, activists and professionals, and also they spread the idea of progress in Galicia.
Keywords: public health; hygiene; hygiene exhibitions; hygiene movement; Lviv; Galicia